Relationship Between Tourism Attractiveness and Marine Park Sustainability - Mohamad, Zaleha; Ramli, Nurhafizah; Muslim, Aidy M; Hii, Yii Siang (International Review of Management and Marketing, 2017)
This paper examines Pulau Tioman tourist views on their appreciation of the marine park as a tool for recreational. Data were collected through quantitative method using questionnaire towards tourist. The results of this study are presented the relationship between attractiveness and sustainability. There are positive relationship between attractiveness and sustainability. The conclusions point to the needs for awareness attractiveness aimed not only at ensuring community engagement within the development of Pulau Tioman but also at generating tourist sustainability at Tioman marine park. Keywords: Tourism Attractiveness, Marine Park, Sustainability JEL Classifications: L83, Q55, Z32